THE IMPACT OF THE EMERGENCE OF ARTIFICIAL INTELLIGENCE (AI) ON THE INDIAN ECONOMY - Singh, Durga Charan (International Journal of Research -GRANTHAALAYAH, 2025)
This study examines the impact of Artificial Intelligence (AI) on the Indian economy, focusing on its sectoral use, macroeconomic implications, and policy dimensions. Using secondary data from government reports, international organizations, and peer-reviewed research literature, this research analyzes how AI is transforming agriculture, manufacturing, services, and governance. Findings indicate that the appropriate use of AI could increase India’s GDP by approximately US600 billion by 2035 by enhancing productivity, enabling financial inclusion, and fostering innovation. However, several challenges remain, including labor market disruption, skills shortages, digital inequalities, and ethical questions related to data governance. The study highlights the duality of AI’s trajectory in India. It can be a driver of growth, while also a potential source of exclusion. Policy recommendations emphasize reskilling programs, open data frameworks, regulatory oversight, and strengthening rural digital infrastructure. Ultimately, the research concludes that if guided by inclusive and ethical policies, AI can be a catalyst for inclusive and sustainable development in India.